This article reveals the phenomenon of national identity, which is an integral part of the development of ethnic community. The concepts of ethnicity, nation and national identity are related. It is shown that the process of formation of a nation and its (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article reveals the phenomenon of national identity, which is an integral part of the development of ethnic community. The concepts of ethnicity, nation and national identity are related. It is shown that the process of formation of a nation and its